On Mathematical Braids - Baldemor, Milagros (Talenta Publisher, 2019)
A braid is any sequence of crossings of the -strand braid with a positive number n, provided none of the strands are self-crossing. The idea is that braids can be organized into groups, in which the group operation is *, which means: â€œdo the first braid on a set of strands, and then follow it with a second on the twisted strandâ€. This study dealt with the formulation of additional basic properties of mathematical braids and the connection of mathematical braids to exponential theorems. Moreover, the researchers developed a program that could generate the total number of crossings and the total number of generators in an n-strand braid with a positive number n.